Sperm Autoantigenic Protein 17 Predicts the Prognosis and the Immunotherapy Response of Cancers: A Pan-Cancer Analysis - Tu, Zewei; Peng, Jie; Long, Xiaoyan; Li, Jingying; Wu, Lei; Huang, Kai; Zhu, Xingen (Frontiers in Immunology, 2022)
Background: Sperm autoantigen protein 17 (SPA17) is a highly conserved mammalian protein that participates in acrosome reaction during fertilization and is a recently reported member of the cancer-testicular antigen (CTA) family. It is reported that the expression of SPA17 is limited in adult somatic tissues and re-expressed in tumor tissues. In recent years, studies have found that it can regulate the progression of a variety of cancers, but its role in cancer immunotherapy is not clear. Methods: The transcriptional data of pan-cancer and normal tissues were acquired from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) datasets. We explored the SPA17 genomic alteration analysis of pan-cancer in cBioPortal. Human Protein Atlas (HPA) and ComPPI websites were used to mine the protein information of SPA17, and western blotting assay was performed to validate the upregulated SPA17 expression in clinical GBM samples. The univariate Cox regression and Kaplan-Meier method were utilized to assess the prognostic role of SPA17 in pan-cancer. Gene Set Enrichment Analysis (GSEA) was applied to search the associated cancer hallmarks with SPA17 expression in each cancer type. TIMER2.0 was the main platform to investigate the immune cell infiltrations related to SPA17 in pan-cancer. The associations between SPA17 and immunotherapy biomarkers were performed by spearman correlation analysis. The drug sensitivity information from Connectivity Map (CMap) dataset was downloaded to perform SAP17 specific inhibitor sensitivity analysis. Findings: SPA17 has expression differences in most cancer types and exhibits prognosis predictive ability in various cancers. In addition, SPA17 is significantly correlated with immune-activated hallmarks, cancer immune cell infiltrations and immunoregulators, and the most interesting finding is that SPA17 could significantly predict anti-PDL1 and anti-PD1 therapy response. Finally, specific inhibitors which correlated with SPA17 expression in different cancer types were also screened by using CMap. Interpretation: The results revealed that SPA17 acts as a robust tumor biomarker. It has functional cytotoxic T lymphocyte (CTL) epitopes suitable for T cell targeting, and participates in additional cell-cell adhesion, which can affect the migration and metastasis of immune cells, and then shape the tumor microenvironment, which might be further applied to develop novel anti-cancer inhibitors.